(untitled) (Siddhajyoti Interdisciplinary Journal, 2021)
Assessment is the key aspect to evaluate learning status of learner’s and academic status of the institution. Assessment practice should be transparent and believable for all. This study intends to assess students’ and teachers’ reflection on assessment based on belief and transparency of assessment. This research is descriptive survey type standing on post positivist paradigm. The major tools of the study are questionnaire and interview. Department of Mathematics Education, Central Department of Education was the study territory. The random sample was used to select the students of third and fourth semester studying on 2076 (2020). There were 12 teachers’ 91 students involved in questionnaire and three teachers and six students for interview. The data were analyzed using weighted mean. Further, data triangulation method was used to get the validity of the research.The findings indicated that there are positive reflections of students and teachers towards the assessment belief and transparency. Therefore, assessment will be more effective if it is planned in a reliable structure for valid results following the transparent criteria of assessment.